Determination of Antioxidant Flavonoids in Sudanese Honey Samples by Solid Phase Extraction and High Performance Liquid Chromatography - Suzan Zein Alabdeen Makawi; Elrasheed Ahmed Gadkariem; Saad Mohamed Hussein Ayoub (E-Journal of Chemistry)
Flavonoids were extracted by solid phase extraction (SPE) from seven floral honey samples of different botanical origin from different regions of Sudan. The flavonoids were determined by high performance liquid chromatography (HPLC) technique using photo diode array detector (PDA). An isocratic and gradient systems for the resolution, identification and quantification of five flavonoids, namely; quercetin, kaempferol, apigenin, hesperetin and isorhamnetin, were developed. Although the isocratic system resolved the five compounds, however it suffered from interference by the complex mixture of honey samples. The gradient system resolved three of five flavonoids, namely, quercetin, kaempferol, and isorhamnetin, without interference by the complex honey matrix. Two flavonoids, apigenin and hesperetin, were observed to elute at close retention times, which lead to their interference with each other when injected in a mixture; however, absorption wavelength selection was found indicative of the presence or absence of either compound. The quantification of these flavonoids was done through the calibration curves of their standards. The obtained results were compared with reported results.